Prairie Christmas - Rice, James 1934- (Austin, Tex. : Shoal Creek Publishers, 1977)
Two lonely cowboys have a mysterious visitor on Christmas Eve.
Keywords: Santa Claus -- Fiction; Cowboys -- Fiction; Christmas -- Fiction; Stories in rhyme; Texas -- Fiction